Breastfeeding History and Risk of Stroke Among Parous Postmenopausal Women in the Women's Health Initiative. Issue 17 (4th September 2018) - Jacobson, Lisette T.; Hade, Erinn M.; Collins, Tracie C.; Margolis, Karen L.; Waring, Molly E.; Van Horn, Linda V.; Silver, Brian; Sattari, Maryam; Bird, Chloe E.; Kimminau, Kim; Wambach, Karen; Stefanick, Marcia L.
Abstract : Background: Stroke is the third leading cause of death among US Hispanic and non‐Hispanic black women aged 65 and older. One factor that may protect against stroke is breastfeeding. Few studies have assessed the association between breastfeeding and stroke and whether this association differs by race and ethnicity. Methods and Results: Data were taken from the Women's Health Initiative Observational Study with follow‐up through 2010; adjusted hazard ratios for stroke subsequent to childbirth were estimated with Cox regression models accounting for left and right censoring, overall and stratified by race/ethnicity. Of the 80 191 parous women in the Women's Health Initiative Observational Study, 2699 (3.4%) had experienced a stroke within a follow‐up period of 12.6 years. The average age was 63.7 years at baseline. Fifty‐eight percent (n=46 699) reported ever breastfeeding; 83% were non‐Hispanic white, 8% were non‐Hispanic black, 4% were Hispanic, and 5% were of other race/ethnicity. After adjustment for nonmodifiable potential confounders, compared with women who had never breastfed, women who reported ever breastfeeding had a 23% lower risk of stroke (adjusted hazard ratio=0.77; 95% confidence interval 0.70‐0.83). This association was strongest for non‐Hispanic black women (adjusted hazard ratio=0.52; 95% confidence interval 0.37‐0.71). Further, breastfeeding for a relatively short duration (1‐6 months) was associated with a 19% lower risk of stroke (adjusted hazard ratios=0.81; 95% confidence interval 0.74‐0.89). This association appeared stronger with longer breastfeeding duration and among non‐Hispanic white and non‐Hispanic black women (test for trend P< 0.01). Conclusions: Study results show an association and dose‐response relationship between breastfeeding and lower risk of stroke among postmenopausal women after adjustment for multiple stroke risk factors and lifestyle variables. Further investigation is warranted.